PENDAMPINGAN USAHA KREATIF KRIPIK KELAPA PADA MASYARAKAT DESA WATUSIPI KECAMATAN ENDE UTARA KABUPATEN ENDE - Reyna Virginia Nona; Aji Sudrajad (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The implementation of community service activities in Watusipi Village was motivated by decreased community income during the pandemic period and the absence of creative efforts by the community to utilize the potential of human and natural resources in the village. It is hoped that the implementation of the KKN Mandiri for a month will provide assistance and build togetherness with village officials and the community to build creative business opportunities that can be done to improve the economic life of the community. One of the superior products of Watusipi village is coconut, so this service activity will be divided into two sub-activities, namely assistance in making coconut chips and assistance in marketing of coconut chips products. This assistance was carried out for three weeks with the target being mothers who are members of the Dasawisma. In the fourth week a survey was conducted to determine the market response to coconut chips products. The achievement of this mentoring activity is quite good because of the active involvement of the participants and the full support of the Village Government, and also from BUMDes, is a seller coconut chip.